2016
DOI: 10.1039/c5ta03389f
|View full text |Cite
|
Sign up to set email alerts
|

Fully spray-coated organic solar cells on woven polyester cotton fabrics for wearable energy harvesting applications

Abstract: a This paper presents the novel use of spray-coating to fabricate organic solar cells on fabrics for wearable energy harvesting applications. The surface roughness of standard woven 65/35 polyester cotton fabric used in this work is of the order of 150 µm and this is reduced to few microns by a screen printed interface layer. This pre-treated fabric substrate with reduced surface roughness was used as the target substrate for the spray-coated fabric organic solar cells that contains multiple layers of electrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 52 publications
0
42
0
Order By: Relevance
“…This system was employed since it forms highly crystalline and sufficiently pure small polymer domains that ensure robust morphology and excellent performance. [88,89] It can be concluded that "bioadvantaged" natural materials can also be integrated into flexible solar cell technologies and help the reduction of no-degrading polymeric elements in the manufacturing. Vanadium oxide (V 2 O x ) was sprayed onto PffBT4T-2OD:PC 70 BM as hole transport layer, followed by the deposition of poly (3,4- Figure 5b.…”
Section: Wwwadvsustainsyscommentioning
confidence: 99%
“…This system was employed since it forms highly crystalline and sufficiently pure small polymer domains that ensure robust morphology and excellent performance. [88,89] It can be concluded that "bioadvantaged" natural materials can also be integrated into flexible solar cell technologies and help the reduction of no-degrading polymeric elements in the manufacturing. Vanadium oxide (V 2 O x ) was sprayed onto PffBT4T-2OD:PC 70 BM as hole transport layer, followed by the deposition of poly (3,4- Figure 5b.…”
Section: Wwwadvsustainsyscommentioning
confidence: 99%
“…This high temperature annealing required for many DSSC's eliminates many common textile materials, but organic PV's offer more choice. Spray coating was used to cover the woven polyester cotton with all the layers for an organic PV, after planarizing the fabric with a screen-printed polyurethane layer [8]. These types of cells require effective encapsulation to prevent atmospheric oxidation of the photoactive polymer.…”
Section: Textile Photovoltaicsmentioning
confidence: 99%
“…This approach provides a low weight solution that minimizes the impact on the feel of the fabric. Integrating these solar cells on textiles requires devices to be flexible, durable and fabrication processes familiar to the textile industry should be used such as screen printing, inkjet printing, spray coating and doctor blading techniques . The DSSC is a sandwich structure that typically comprises two fluorine tin oxide (FTO) coated conducting glass overlapped together with liquid redox electrolyte injected in between them .…”
Section: Introductionmentioning
confidence: 99%
“…These devices were fabricated using both spray coating and doctor blading techniques. Previously, the authors have demonstrated a fully spray coated OSCs on glass and fabric substrates that achieved low PCEs of 0.1% and 0.02%, respectively . After optimizing the functional layer thicknesses, the PCE has been improved values of 3.9% and 1.23% on glass and fabric substrates respectively .…”
Section: Introductionmentioning
confidence: 99%